Highly Efficient Deep‐Blue Electrophosphorescent Pt(II) Compounds with Non‐Distorted Flat Geometry: Tetradentate versus Macrocyclic Chelate Ligands. (12th December 2016) - Wang, Xiang; Peng, Tai; Nguyen, Carmen; Lu, Zheng‐Hong; Wang, Nan; Wu, Wenjie; Li, Quansong; Wang, Suning
Abstract : A new class of deep blue electrophosphorescent Pt(II) emitters have been designed and synthesized. This new class of deep blue Pt(II) emitters employ tetradentate and macrocyclic chelate chromophores to constrain the Pt(II) molecules in a non‐distorted flat geometry in both the ground state and the excited state. The new deep blue emitters do not produce excimer emission, with emission quantum efficiency as high as 95% in 10% doped PMMA (poly(methyl methacrylate) films, and excellent UV stability, compared to the corresponding bidentate Pt(II) emitters. The macrocyclic tetradentate chelate Pt(II) compounds are the first examples of fully sterically constrained deep blue Pt(II) emitters that do not display structural distortion and have a higher thermal stability and a higher emission quantum efficiency than the corresponding non‐macrocyclic tetradentate Pt(II) analogues. A computational study supports that the macrocylic Pt(II) compounds are structurally more stable than the tetradentate Pt(II) molecules. Bright and efficient deep blue electrophosphorescent devices using a macrocyclic Pt(II) emitter have been successfully fabricated with a maximum brightness of 10 680 cd m −2, maximum external quantum efficiency of 15.4% (at 490 cd m −2 ), and Commission Internationale de L'Eclairage (1931) coordinates ( x + y ) of less than or near 0.30, respectively. Abstract : Highly efficient Pt(II) deep‐blue emitters with tetradentate and macrocyclic chelate ligands and non‐distorted structures have been achieved. Full steric constraint has been found to play an important role in structural stability in the excited state and the performance of the new deep blue emitters in organic light‐emitting diodes.